2010
DOI: 10.5688/aj740223
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Pharmacy Education Concentration on Students' Teaching Knowledge and Attitudes

Abstract: Objective. To describe the introduction of an education concentration in a doctor of pharmacy (PharmD) program and to evaluate its impact on students' knowledge and attitudes about teaching. Design. A concentration consisting of 3 elective 2-credit didactic courses and an advanced pharmacy practice experience with a teaching focus were developed and implemented into the PharmD curriculum.Assessment. An attitudes survey instrument and knowledge test were administered to students enrolled in the education concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…79 There is considerable variability in residents' exposure to teaching and to opportunities in academia. 80 The grams should be offered to preceptors of introductory and advanced pharmacy practice experiences (IPPEs and APPEs) that not only improve quality in teaching and precepting, but also stimulate interest for practitioners to pursue faculty positions. Other areas integral to faculty member recruitment and retention have not been explored thoroughly.…”
Section: Faculty Recruitment and Retentionmentioning
confidence: 99%
“…79 There is considerable variability in residents' exposure to teaching and to opportunities in academia. 80 The grams should be offered to preceptors of introductory and advanced pharmacy practice experiences (IPPEs and APPEs) that not only improve quality in teaching and precepting, but also stimulate interest for practitioners to pursue faculty positions. Other areas integral to faculty member recruitment and retention have not been explored thoroughly.…”
Section: Faculty Recruitment and Retentionmentioning
confidence: 99%
“…In a previous study in which pharmacy students participated in 3 educational elective courses, the authors demonstrated increased knowledge and teaching skills, but only some of the results were statistically significant. 16 We believe the overall success of our program was due to the rigorous TA responsibilities and the ongoing mentorship provided by PCL faculty members. Our program involved many components including weekly small-group facilitation, grading, weekly TA meetings, American Journal of Pharmaceutical Education 2016; 80 (9) Article 149.…”
Section: Discussionmentioning
confidence: 95%
“…Some opportunities offered by institutions to stimulate pharmacy student knowledge and interest in academia include teaching electives and advanced pharmacy practice experiences (APPEs). [13][14][15][16] Nonetheless, additional educational opportunities are needed to encourage students to consider a career in academic pharmacy. Student teaching programs may meet the goal of furthering student knowledge of academic pharmacy.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, if there are enough programmatic strengths or instructors with common interests, elective sequences or concentrations can be developed. Topics for elective concentrations might include research, 9 leadership, 10 academia, 11 or specialized clinical focus areas. 12 These concentrations may involve partnering with other health professions for interprofessional design and delivery.…”
Section: Partnering With Students and Providing A Sandbox For Facultymentioning
confidence: 99%